MEWUJUDKAN SEKOLAH UNGGUL: EVALUASI STANDAR GTK DAN SARPRAS DI SDIT CAHAYA HATI PAUH KAMBAR - Merri Yelliza; Mulya Syafrina; Putri Yulia Mandasari; Wendri Gusdi; Emi Sofia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research evaluates the fulfillment of standards for Teachers and Educational Personnel (GTK) and facilities (sarpras) at SDIT Cahaya Hati Pauh Kambar, Padang Pariaman, West Sumatra. Using literature review and field observation methods, this study found that GTK has met the basic competency standards, although certification and professional training need to be improved. Facilities such as classrooms, libraries, and internet access are available, but there is still no science laboratory. Recommendations include enhancing GTK development and providing supporting facilities for 21st-century learning.